Alkali-catalyzed hydrothermal treatment of sawdust for production of a potential feedstock for catalytic gasification. (1st December 2018) - Imai, Akihisa; Hardi, Flabianus; Lundqvist, Petter; Furusjö, Erik; Kirtania, Kawnish; Karagöz, Selhan; Tekin, Kubilay; Yoshikawa, Kunio
Highlights: The effect of temperature and catalyst loading on product distributions from HTT were investigated. The heating values of the produced slurry ranged from 12.0 to 16.4 MJ/kg. The product yield of solid residue ranged from 55.6 to 81.5 wt%. The highest combustibles were obtained with solid residue products. The yield of aqueous products ranged from 11.1 to 34.3 wt%. Abstract: This study investigates the effects of reaction temperature and catalyst loading on product yields and fuel properties of produced slurry during the alkali catalyzed hydrothermal treatment (HTT) of pine sawdust. The yield of the liquid fraction, or the aqueous product (AP), at process temperatures of 180–260 °C obtained after solid/liquid separation of the slurry ranged from 11.1 to 34.3 wt% on a dry, ash free basis. The fuel quality of the produced slurry, such as the elemental composition and the higher heating value (HHV), was mainly affected by the catalyst loading. An increase in the catalyst loading caused the ash content to increase. Although the increase in temperature leads to a higher liquid fraction in the slurry making it more homogeneous, its contribution to the elemental composition of the whole slurry was limited. HHV of the produced slurry ranged from 12.0 to 16.4 MJ/kg. These values are comparable to that of black liquor (BL), which has previously been shown to be a promising feedstock for gasification in a pilot scale entrained flow gasifier. These results imply the possibility of a fuel switch from BL to the HTT slurry for entrained flow gasification though its gasification reactivity and conversion characteristics must be investigated further.